Implementasi SAK Entitas Privat dan Implikasinya terhadap Prosedur Audit: Perspektif Auditor - I Kadek Jonh Stiawan (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
The implementation of SAK EP has introduced changes in the recognition, measurement, and disclosure of private entities’ financial statements, which directly affect audit practices. These changes not only influence the preparation of financial statements but also require auditors to adjust the audit procedures applied. This study aims to analyze the implementation of SAK EP from the auditor’s perspective and to examine its implications for audit risk assessment, audit planning, substantive testing, and the evaluation of internal control. The study adopts a qualitative approach using a descriptive exploratory method. Data were collected through in-depth interviews with auditors involved in private entity audit engagements, supported by documentation and a review of relevant accounting standards. The findings indicate that the implementation of SAK EP increases audit complexity, thereby encouraging a more intensive risk-based audit approach through more detailed audit planning, enhanced substantive testing, and stricter evaluation of internal control. Although it increases audit workload and audit time, these procedural adjustments contribute to improved audit quality and greater reliability of private entities’ financial statements